2009 IEEE Conference on Electrical Insulation and Dielectric Phenomena 2009
DOI: 10.1109/ceidp.2009.5377719
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tracking in cycloaliphatic epoxy based nano structured composites

Abstract: This investigation is dedicated to the development of a new class of nanostructured composite material from cycloaliphatic epoxy polymers with nanoclay and microsilica as the fillers and the analysis of the behavior associated in the inclined plane tracking test (IEC 60587). Composite materials with different weight percentages of fillers were prepared and subjected to electrical tracking according to the standard. XRD and SEM measurements were carried out to study the dispersion of the fillers and the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…6 For example, addition of 1-2.5 wt% nanoclay into the epoxy matrix made them more resistant to tracking, since the exfoliated clay acted as a barrier and limited tracking, while the pure polymer burnt vigorously during the tests. 7 Similar effects on the tracking properties were reported for various ame retardants in poly(butylene terephthalate). 4 The ammability and CTI tests also conrmed that diethylphosphinic acid aluminum salt which forms condensed form of char enhances the ame retardant properties.…”
Section: Introductionsupporting
confidence: 63%
“…6 For example, addition of 1-2.5 wt% nanoclay into the epoxy matrix made them more resistant to tracking, since the exfoliated clay acted as a barrier and limited tracking, while the pure polymer burnt vigorously during the tests. 7 Similar effects on the tracking properties were reported for various ame retardants in poly(butylene terephthalate). 4 The ammability and CTI tests also conrmed that diethylphosphinic acid aluminum salt which forms condensed form of char enhances the ame retardant properties.…”
Section: Introductionsupporting
confidence: 63%
“…Data hasil pengukuran arus bocor dengan kontaminan NH4Cl dan air hujan ditunjukkan pada tabel 6. Gelombang arus bocor sinus hasil pengukuran menunjukkan adanya arus bocor yang mengalir pada permukaan isolator sehingga terjadinya kenaikan suhu pada permukaan yang menunjukkan partikel silika mengalami pembakaran [11]. Gambar 16.…”
Section: Pengukuran Arus Bocorunclassified
“…For safety reasons and consideration factors towards the detrimental health of the insulation systems researchers are showing keen interest on surface degradation and dielectric breakdown of the polymeric insulating materials. Guastavino et al [18] performed tracking test on different wt% of nanoclay and microsilica filled epoxy composites. They concluded that 1 wt% nanoclay with 53.5 wt% silica and 2 wt% nanoclay with 53 wt% silica composites showed better resistance to tracking.…”
Section: Introductionmentioning
confidence: 99%